Pengaruh Islamic Corporate Social Responsibility Dan Sharia Governance Terhadap Kinerja Keuangan Perusahaan - Rimi Gusliana Mais; Munir Munir; Nuryasa Nuryasa (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
This study aims to determine the effect of Islamic Corporate Social Responsibility and Sharia Governance on the financial performance of Islamic companies listed on the Indonesian Sharia Stock Index in 2018-2021.This study uses a quantitative approach associative research, which is measured using a panel data regression-based method with the help of Software Eviews 12. The population of this study are companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2018-2021 period. The sample was determined based on purposive sampling with a total sample of 28 companies so that the total observations in this study were 112 observational data. The data used in this study are secondary data obtained by downloading the annual report on the official website of each company and testing using the t test (partially).The results show that (1) Islamic Corporate Social Responsibility has no effect on the company's financial performance (ROA) in companies listed on ISSI for the 2018-2021 period, (2) Sharia Governance has a significant positive effect on the company's financial performance (ROA) listed on ISSI. period 2018-2022.